Pengaruh Penggunaan QRIS Dan Kepuasan Konsumen Terhadap Keputusan Pembelian Produk UMKM Di Kabupaten Mamuju - Nurananda, Nurananda; Fajariani, Nur; Tamin, Tamin (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This research aims to analyze the effect of QRIS usage and consumer satisfaction on the purchase decision of MSME (Micro, Small, and Medium Enterprises) products in Mamuju Regency. The study employed a quantitative method with an associative approach. The population consisted of people who had purchased MSME products in Mamuju Regency. The sampling technique used was purposive sampling, with a sample size of 96 respondents determined using the Lemeshow formula. Data collection was performed through observation, interviews, documentation, and the distribution of questionnaires. Data analysis utilized multiple linear regression, with hypothesis testing involving partial tests (t-test), simultaneous tests (F-test), and the coefficient of determination (R²) analysis. The results show that: (1) QRIS usage has a partially significant effect on the purchase decision of MSME products in Mamuju Regency; (2) Consumer satisfaction has a partially significant effect on the purchase decision of MSME products in Mamuju Regency; and (3) QRIS usage and consumer satisfaction have a simultaneously significant effect on the purchase decision of MSME products in Mamuju Regency. The combined contribution of these two variables is 33.4%, which is categorized as low. This indicates that 66.6% of the variability in the purchase decision of MSME products in Mamuju Regency is influenced by other variables outside of this model.